A Correction: Economics and Insurance - Little, L. T. (Review of Economic Studies, 1938)
Economics and Insurance: A Correction The Review of Economic Studies, Volume 5, Issue 2, February 1938, Page 157, https://doi.org/10.2307/2967531 Published: 01 February 1938